Thermography study of nipple-areola complex in immediate puerperas - Migueli, Maria Ferreira di; Luz, Soraia Cristina Tonon da; Santos, Keyla Mara dos; Honório, Gesilani Julia da Silva; Roza, Thuane da (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: In the puerperium period, one of the main causes for discontinuation of breastfeeding is breast changes. The fissure is characterized by a skin lesion in the nipple-areolar complex, a consequence of an error in the breastfeeding. Objective: The present study aimed to identify the surface temperature of the nipple-areola complex of the lactating breast, with and without fissure, establishing a comparison with a group of nulliparous women. Method: The sample consisted of thirty women, forming three groups: G1- puerperae with breast fissure; G2- puerperae without breast fissure; and G3- nulliparous. The evaluations were carried out at public Carmela Dutra Maternity of Florianopolis (SC), consisting of: interview, inspection and thermographic examination of the anterior view of the breasts. Nulliparous were evaluated at the Santa Catarina State University. Results: Increased vascularization was observed in G1 and G2, including the nipple-areola complex, mainly in G2. Seven women of G1 and eight of G2 presented warmer and vascularized areolar region when compared to the nipple. The nulliparas presented different thermal image, with smaller number of areas with delineations of blood vessels. Statistical differences were observed between groups at the minimum temperature in the areola (p=0.007) and in the nipple (p=0.037). When comparing the mean temperatures between the groups, there was a statistical difference between G1 and G3 in both regions (p=0.005; p=0.047). The G1 presented lower temperature in the nipple region. Conclusion: The group with fissure had lower values of superficial temperature compared to the others, which could be associated with a vascular alteration process, and the thermographic evaluation made it possible to identify physiological and structural modifications of the breast. As a non-invasive technique, thermography can be a tool in the monitoring of physiological anatomical changes of the breast, as well as in the identification of problems related to lactation difficulty, opening doors to new studies about the subject.